More visible but limited in its popularity: atheism (and atheists) in Finland - Taira, Teemu (Approaching Religion, 2012)
This paper argues that atheism has become more visible in Finland, but it is a relatively unpopular identity position. The relatively low popularity of atheism is partly explained by the connection between Lutheranism and Finnishness. In public discourse atheism has been historically connected to communism and the Soviet Union (and, therefore, anti-Finnishness). However, atheism has slowly changed from being the other of Finnishness to one alternative identity among many, although it has not become extremely popular. Recently, with the rise of the so-called ‘New Atheism’, atheism has become more visible in Finnish society and this development has led to a polarised debate between defenders and critics of religion. Despite being a study on locality, the aim is to develop a methodological approach that can be applied to other contexts.